Bees of the genus Panurginus in Siberia, Far East of Russia, and Allied Areas (Hymenoptera: Andrenidae, Panurginae) - Romankova, Tatiana G.; Astafurova, Yulia V. (Zootaxa, 2011)
The genus Panurginus Nylander of the Asian part of Palearctic is revised for the first time. 14 species are listed for Siberia, the Far East of Russia, Kazakhstan, Mongolia, and Northern China. Lectotypes for P. alticolus F. Morawitz, 1876, P. herzi F. Morawitz, 1891 and P. labiatus Eversmann, 1852 are designated. Panurginus niger Nylander, 1848, the type species of the genus, was studied for the first time after it was described. Panurginus dubius Osytchnjuk, 1995 is a junior synonym of P. niger Nylander, 1848. Panurginus alticolus, P. crawfordi Cockerell, 1914, P. herzi F. Morawitz, P. labiatus, P. romani Aurivillius, 1914, P. niger and P. nigripes F. Morawitz, 1880, are redescribed and seven new species are described: P. alpotanini, P. arsenievi, P. kozlovi, P. kropotkini, P. mikhno, P. muraviovi, P. obruchevi. In Russia, P. alticolus and P. labiatus are first recorded for Siberia; P. alticolus is a new record, and one species is newly described from Kazakhstan; P. niger and P. herzi are first recorded, and two species described from Mongolia. A key to the 14 species with 118 illustrations, and annotated list along with data on types, synonymies, general geographical distribution, the material examined and descriptions for all species is presented.